PROPUESTA DE INDICADORES PARA EVALUAR EL VALOR ECOLÓGICO DE HUMEDALES COSTEROS DE LIMA Y CALLAO - Jurado, Maura (2025)
The conservation status of an ecosystem can be measured by its ecological value. As part of a series of regulations within the framework of the National Environmental Impact Assessment System, the Environment Ministry of Peru has published the methodologie to calculate the ecological value of highland ecosistems in the "Complementary Guide for Environmental Compensation: High Andean Ecosystems”. Currently, there are guides for assessing the status of conservation of certain types of ecosystems; however, there is still no guide that defines the ecological indicators and attributes for coastal wetlands. This study proposes eight indicators, considered as suitable for calculating the ecological value of coastal wetlands in Peru, selected through a suitability index. As an application example, the ecological value of four wetlands in Lima and Callao were calculated: Pantanos de Villa, Ventanilla, Santa Rosa and Puerto Viejo, using information from secondary and primary sources (interview with experts). Considering Pantanos de Villa, as the reference ecosystem with a "very good" ecological value, it was found that Santa Rosa, Ventanilla and Puerto Viejo Wetlands presented a "good" ecological value. In addition, a positive correlation, although non-significant, was found between the ecological value and the environmental management level. The proposed ecological indicators can be used to calculate the ecological value of other wetlands along the coast of Peru, to prepare technical documents or researches on the state of conservation, monitoring, rehabilitation, restoration or compensation of coastal wetlands, contributing to their proper management and conservation.